PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PENGGUNAAN MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS YOUTOBE DI SMP N. 8 PADANGSIDIMPUAN - Freski Detra Silaban; Rahmatika Elindra; Muhammad Syahril Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aims to improve students’ mathematical problem solving ability on the topic of solid through using blended learning based on you tube of SMP Negeri 8 Padangsidimpuan. The research was conducted by applying Class Action Research (CAR) with 25 students as the subject (class VIII-1 SMP Negeri 8 Padangsidimpuan). Instrument of the research was test and observation. The research consists of two cycles. The first cycle showed the average of test of the students’ mathematical problem solving ability on the topic of solid was 74.59 (48% students got passing grade) and the average of observation sheets showed 87.53 (very good category). Furthermore, the second cycle showed the average of the test was 86.24 (88% students got passing grade) and the average of observation sheets was 94.42 (very good category). It’s concluded blended learning based on you tube was able to improve students’ problem solving ability of SMP Negeri 8 Padangsidimpuan.